Physicochemical and Microbiological Analysis of Stingless Bees Honey Collected from Local Market in Malaysia - Wan Nadja Julika; Azilah Ajit; Ahmad Ziad Sulaiman; Aishath Naila (Indonesian Journal of Chemistry, 2019)
The growing demand for honey in the market has led to the occurrence of the tampering honey with foreign substances and increases the production of artificial honey. Due to this concern, this study works on the physicochemical and microbial characterization of stingless bee honey. The physicochemical analysis showed that the honey possessed pH (2.51–3.26), free acidity (121.1 to 318.7 meq/kg), moisture (19.4–30.9%), electrical conductivity (0.33–0.69 mS/cm), ash content (2.75–4.31 g/100g), Hydroxymethylfurfural (HMF) content (35.4 to 461.7 mg/kg) and diastase activity (2.71 to 6.11 DN). Also, sugar profile of honey showed that the honey contained fructose (15.03–32.52 g/100g), glucose (12.17–34.55 g/100g) and sucrose (0.01–7.29 g/100g). The harvested honey, H1, and H2 have the highest potential to become an antibacterial agent to treat disease compared to commercial honey samples because they were active against Gram-negative bacteria. All analyzed samples were within the maximum limit of the quality criteria set by the Malaysian Kelulut Standard and Codex Alimentarius except for free acidity, HMF, and Diastase Number. All the data obtained is vital in order to create a specific statute for stingless bees honey in Malaysia that may help to protect the consumer from purchasing adulterated honey.